PENGGUNAAN MEDIA KARTU BERGAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS II SDN 067 PEKANBARU - Eka Ramadhan Sari; Otang Kurniaman (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
This research was motivated by the low reading ability of second-grade students at SDN 067 Pekanbaru. The low reading ability was caused by the teachers’ limited use of learning media, which resulted in a monotonous learning process and differences in students’ abilities. One type of learning media that can be utilized to improve reading skills is flashcard media. Flashcard media is a reading medium in the form of cards containing pictures accompanied by words. This study aimed to improve the reading skills of second-grade students at SDN 067 Pekanbaru through the use of flashcard media. The research employed a classroom action research design, with the research subjects consisting of 24 students of grade II at SDN 067 Pekanbaru. The results showed an increase in teacher activity, where in cycle I the first meeting reached a percentage of 70.83% and increased to 75% in the second meeting. In cycle II, teacher activity further increased to 83.33% in the first meeting and 87.5% in the second meeting. Student activity also showed improvement, with a percentage of 70.83% in the first meeting of cycle I and increasing to 79.17% in the second meeting. In cycle II, student activity increased to 87.5% in the first meeting and further rose to 91.67% in the second meeting. The improvement in students’ reading ability was indicated by the increase in the average score, which rose from the initial score of 63.75 to 73.88 in cycle I, representing an improvement of 15.89%, and further increased in cycle II to 83.96, with an improvement percentage of 31.70%.